Using “Digital Black Hole” to Help Student in Learning Arithmetic and Enhance Students' Interest in Learning - Jihe Chen; Ying Zhou; Qiulian Zhao (Departement of Mathematics Education, 2020)
For most students, mathematics is difficult, boring, and not fun. However, mathematics is of great help in terms of academic performance and the development of students' calculation ability and abstract logical thinking. So how to make students like mathematics? How to improve students' mathematical ability? In response to these two doubts, this article designed the following teaching links based on HPM. The research method in this research is descriptive qualitative by describing the lesson plan on arithmetic material. The sample and population were grade 3, Elementary school, in Guilin, China. The results showed that in the real class, it was found that students were very interested in the